Establishment of deformable three‐dimensional printed models for laparoscopic right hemicolectomy in transverse colon cancer. Issue 7 (26th February 2021) - Hojo, Daisuke; Kawai, Kazushige; Murono, Koji; Nozawa, Hiroaki; Hata, Keisuke; Tanaka, Toshiaki; Nishikawa, Takeshi; Shuno, Yasutaka; Kaneko, Manabu; Sasaki, Kazuhito; Emoto, Shigenobu; Ishii, Hiroaki; et al.
Abstract: Background: Applications of three‐dimensional (3‐D) printed solid organ models for navigation and simulation were previously reported for abdominal surgeries, and their usefulness was shown by subjective evaluation. However, thus far, no study has examined the effect of intraoperative movements for tissue handling. Novel, deformable 3‐D printed models of the superior mesenteric artery (SMA) and superior mesenteric vein (SMV) were created to optimize laparoscopic right hemicolectomy. The aim of this study was to establish a method using these individualized models for use in surgical practice. Methods: Deformable 3‐D models for laparoscopic right hemicolectomy were created using a 3‐D printing flexible filamentous material (thermoplastic polyurethane). Five patients with transverse colon cancer who underwent laparoscopic right hemicolectomy with D3 lymphadenectomy between April 2017 and September 2019 were enrolled in this study. Then, the created patient‐specific models were compared with the previously recorded intraoperative video views. Results: Transverse colon mobilization changed the spatial arrangement of the branches of the SMA and SMV. The 3‐D models reproduced the intraoperative view, although approaches to the dominant vessels to complete D3 lymphadenectomy may vary. Conclusions: Deformable 3‐D models of the SMA and SMV with added branches may aid in optimizing laparoscopic right hemicolectomy operations. Abstract : Novel, deformable three‐dimensional (3‐D) printed models of the superior mesenteric artery and superior mesenteric vein were created to optimize laparoscopic right hemicolectomy. In five patients with transverse colon cancer who underwent laparoscopic right hemicolectomy, the 3‐D models reproduced the intraoperative view, although approaches to the dominant vessels to complete D3 lymphadenectomy may vary. Deformable 3‐D models of superior mesenteric artery and superior mesenteric vein with added branches may aid in optimizing laparoscopic right hemicolectomy operations.